Effectiveness of Nurses' Knowledge of Surgical Asepsis: Results from a Structured Questionnaire - Sengupta, Manashi; Kharsamai, Amanda (Medical Research and Its Applications Vol. 8, 2024)
Introduction: Asepsis is the state of not being infected or coming into touch with microbes. Surgical asepsis is a collection of certain techniques and procedures carried out in closely monitored environments with the intention of reducing pathogen contamination. It uses asepsis maximization and maintenance, infection prevention for patients, and pathogen containment. Objectives: The present study finds out the effectiveness of structured teaching programme on knowledge and practice regarding surgical asepsis among 3rd-year B.Sc Nursing students. Materials and Methods: The research approach and design adopted for this study is a quantitative pre-experimental one-group pre-test post-test design. The study was conducted at the Faculty of Nursing, Assam down town University among 3rd year B. Sc Nursing students. Fifty-seven (57 nos.) of 3rd year B. Sc. Nursing students were selected by using a non-probability purposive sampling technique. The tools used were a Self-Structured knowledge questionnaire (total no. of items was 20) and an observational checklist to assess knowledge and practice regarding surgical asepsis. Descriptive and Inferential statistics were used to analyze the data. The frequency and percentage were calculated to assess the knowledge and practice of the students. Results: Results revealed that 46 nos. of students (80.70%) had average knowledge and 11nos. (19.30%) had good knowledge whereas in the post test after the implementation of the Structured Teaching Programme, 52nos. (91.23%) had good knowledge and 5nos (8.77%) had average knowledge regarding surgical asepsis. 54 nos. (94.74%) had moderate practice, 2nos of students (3.51%) had poor practice and 1 student (1.75%) had good practice and in the post-test after the Structured Teaching Programme, 54nos. (94.74%) had good practice and 3nos. (5.26%) had moderate practice regarding the two aspects of surgical asepsis (Hand Scrubbing and Gloving). The study showed highly significant differences between the pre-test and post-test of the study group at p<0.01 for overall total nurses’ practices concerning aseptic techniques in the operating room, this means there are high level of improvement in nurses’ practice for the study group between pre-test and post-test interventional program about aseptic techniques in operating room. Conclusion: A structured teaching programme was found to be effective in improving the students’ knowledge which ultimately improves their practice in surgical asepsis. Nursing Curriculum among the students and staff, especially emphasizing its practice and maintenance will help to improve health and prevent infection among patients thus optimizing quality care.